ACINETOBACTER BAUMANNII PNEUMONIA ASSOCIATED WITH MECHANICAL VENTILATION DUE TO COVID-19: EPIDEMIOLOGY, CLINICAL CHARACTERISTICS AND THERAPY - Gazibara, Tatjana (Medicinska istraživanja, 2024)
Less than 3% of people who catch COVID-19 need hospital treatment. However, up to one-third of hospitalized patients with COVID-19 require invasive mechanical ventilation. Ventilator-associated pneumonia (VAP), caused by the multidrug-resistant Acinetobacter baumannii (A. baumannii), is an emerging infection in the intensive care units and can have fatal consequences for those patients who already have critical COVID-19. Countries of the Balkan peninsula have an exceptionally high prevalence of invasive carbapenem-resistant Acinetobacter spp in the hospital setting. Diagnosing this type of pneumonia is a challenging process. Furthermore, treatment complexities arise because of multidrug resistance. Novel therapeutic agents, such as sulbactam/durlobactam and zosurabalpin could be the new therapeutic opportunity for A. baumannii-induced VAP. Antimicrobial resistance of A. baumannii is not entirely understood, although several mechanisms have been identified. To adequately manage VAP it is important to isolate causative agents, have an awareness of the resistance pattern, carefully dispense antibiotics and identify risk factors. In this review, we discuss epidemiological characteristics, pathophysiological mechanisms, clinical presentation and diagnosis, as well as the current and novel treatments of A. baumannii-induced VAP.
Keywords: COVID-19; Ventilator-associated pneumonia; Acinetobacter baumannii; multidrug resistance